The Wooden Church “Saint Hierarch Nicholas” – a historical monument and a symbol of spiritual culture - Tudor Arnăut; Elena Vorotneac (Codrul Cosminului, 2011)
The present study is dedicated to the research of the wooden churches built in the XVIII-th century in Bessarabia. The authors refer, in particular, to the church „Saint Hierarch Nicholas” from Musteaţa village, Făleşti district. This is one of the few monuments from Republic of Moldova of such historical importance and it is a relevant spiritual symbol of Romanian culture. The church „Saint Hierarch Nicholas” is distinguished by its complex rustic architecture with a reach symbolism load. It is a typical monument according to the “peasant house” category, with no cupola. It is built of wood on a stone foundation. According to archival documents, it was set in 1757, when the village was called Oişeni. Currently, the building is in a damaged condition. It is necessary emergency restoration and conservation of the monument. Our goal is to capitalize on historical and spiritual importance of this monument for the Romanian’s culture from everywhere.